Pengembangan Sistem Informasi Manajemen Berbasis Teknologi Terkini - Nuragustin Nuragustin; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2023)
Management Information Systems (MIS) are the main foundation in the operations of an organization. With the development of technology, SIM based on the latest technology is an important key in improving efficiency and productivity. This article discusses the essence of the latest technology-based SIM, explainingits benefits, and analyze the challenges that may occur in its implementation. This research too explores several case studies about the success of recent MIS development in organizations leading. Ultimately, this article concludes with recommendations for SIM-based implementationthe latest technology to optimize managerial performance.